1994
DOI: 10.1016/s0006-3495(94)81007-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of lignin formation at the molecular level by scanning tunneling microscopy

Abstract: A scanning tunneling microscope (STM) was used to observe the temporal formation and organization of dehydrogenative polymer (DHP) synthesized from coniferyl alcohol. The images obtained elucidate this structure for the first time. The structure of DHP, as seen from STM images, shows long-range order. It appears that DHP consists of building units or modules assembled into larger assemblies called supermodules. Supermodules are interconnected into the overall lattice-like polymer structure with or without sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 15 publications
5
32
2
Order By: Relevance
“…This has been recently determined by gel permeation chromatography. This observation is also consistent with a lower degree of structural order in PCP than in DHP, as observed in films formed on both polymers by STM in the nanoscale range (13,14).…”
Section: Resultssupporting
confidence: 85%
“…This has been recently determined by gel permeation chromatography. This observation is also consistent with a lower degree of structural order in PCP than in DHP, as observed in films formed on both polymers by STM in the nanoscale range (13,14).…”
Section: Resultssupporting
confidence: 85%
“…There is a slight discrepancy between previously published STM results (Radotic et al 1994) and herein presented ESEM images of fragments of a globule surfaces. While STM images reveal the modular structure of the globule, ESEM images show a smooth surface of a globule.…”
Section: Resultscontrasting
confidence: 99%
“…This value is calculated for an assumed polymer density of 1.3 g/cm 3 . However, the experimentally determined molecular mass of the DHP lignin model compound is on the order of magnitude of 10 5 (Radotic et al 1994, Wayman et al 1974, which is six orders of magnitudes less than previously indicated in the calculated value based on the average size of the observed globules. We strongly believe that this discrepancy can be explained in terms of the modular structure of the globule.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…However, a globular object is not a fractal [13]. To reconcile the fractal properties of lignin, it is assumed that lignin adopts a coiled or helical conformation possessing fractal dimensions [131,141,145,146].…”
mentioning
confidence: 99%